Bronchioloalveolar carcinoma in young people - Lis, Adam; Zalewska, Agnieszka; Nykiel-Nalepa, Elwira; Kaznowska, Ewa; Kobak, Grzegorz; Rzeszutko-Grabowska, Magdalena; Kaziród, Tomasz; Kądziołka, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2002)
Bronchioalveolar carcinoma is a well-differentiated adenocarcinoma, localized primary on the periphery of the lungs, extrabronchially, showing tendency to spread through lymph vessels and air spaces, with no evident destruction of walls of bronchioles and alveoli. It constitutes histogenetically a non-homogenous group of neoplasms, in which three main categories are distinguished: mucinous, scirrhous and nonmucinous carcinoma. Bronchioalveolar carcinoma is the most invasive adenocarcinoma of the lungs and represents 3% of all lung cancers. Occurrence of bronchioalveolar carcinomas does not depend on gender; 30% of patients suffering from the cancer never smoked tobacco. They are usually patients between 40 and 70 years of age. Over half of them are asymptomatic and radiological changes on X-rays of the chest are discovered accidentally during routine examinations. If symptoms appear, they are non-characteristic. Hemoptysis, which appears in less than 10% of the patients and severe hypoxemia are the late symptoms and concern particularly disseminated forms of bronchioalveolar carcinoma. Bronchioalveolar carcinoma manifests itself radiologically as: a single, well-deliminated, peripheral tumor; micronodular disseminated forms or as segmental or lobar consolidations. Radiological feature that distinguishes bronchioalveolar carcinoma is occurrence of air bronchogram, that is not observed in the case of other types of lung cancers. The treatment depends on advancement of the lesions. In the case of a single tumor in the 1st or 2nd stage according to TNM classification, lobectomy with lymph nodes is a treatment of choice. In the case of disseminated forms, systemic chemotherapy is used. Prognosis in bronchioalveolar carcinoma is better than in other types of non-small cell carcinomas, but in the case of disseminated forms is unfavorable. In the article two cases of bronchioalveolar carcinoma are presented: the first one in a 30-year-old male admitted for diagnostic evaluation of disseminated lesions found in roentgen image of the thorax and the second one in a 17-year-old female diagnosed because of presence of features of the middle lobe syndrome.